STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MEMPENGARUHI PENDIDIKAN KARAKTER ISLAM DI KABUPATEN SORONG, PAPUA BARAT DAYA - Muhammad Arsyad Ambo Tuo; Jumrana B (Pascasarjana IAIN Sorong, 2026)
Islamic character education is a strategic priority in Indonesian madrasahs, particularly in multicultural regions facing ethnic diversity, religious pluralism, modernization, and limited educational resources. This qualitative study explores the leadership strategies of Madrasah Tsanawiyah (MTs) principals in Sorong Regency, Southwest Papua, focusing on leadership practices, influencing factors, and educational outcomes. Fifteen participants, including principals, teachers, students, and community members, were selected purposively. Data were collected through semi-structured interviews, observations, and document analysis and were analyzed using thematic analysis. The findings reveal that principals employ transformational, spiritual, participative, and exemplary leadership by integrating Islamic values into school culture, curriculum, religious activities, and community partnerships. Effective implementation is supported by teacher commitment, parental involvement, and community collaboration but constrained by limited facilities, technological distractions, multicultural challenges, and inconsistent parental supervision. These leadership strategies significantly strengthen students’ religious commitment, discipline, honesty, responsibility, and social engagement, fostering sustainable Islamic character education in multicultural madrasahs.